Trends in outcomes of women with myocardial infarction undergoing primary angioplasty—Analysis of randomized trials - Motovska, Zuzana; Hlinomaz, Ota; Aschermann, Michael; Jarkovsky, Jiri; Želízko, Michael; Kala, Petr; Groch, Ladislav; Svoboda, Michal; Hromadka, Milan; Widimsky, Petr (Frontiers in Cardiovascular Medicine, 2023)
Background Sex- and gender-associated differences determine the disease response to treatment. Aim The study aimed to explore the hypothesis that progress in the management of STE-myocardial infarction (STEMI) overcomes the worse outcome in women. Methods and results We performed an analysis of three randomized trials enrolling patients treated with primary PCI more than 10 years apart. PRAGUE-1,-2 validated the preference of transport for primary PCI over on-site fibrinolysis. PRAGUE-18 enrollment was ongoing at the time of the functional network of 24/7PCI centers, and the intervention was supported by intensive antiplatelets. The proportion of patients with an initial Killip ≥ 3 was substantially higher in the more recent study (0.6 vs. 6.7%, p = 0.004). Median time from symptom onset to the door of the PCI center shortened from 3.8 to 3.0 h, p < 0.001. The proportion of women having total ischemic time ≤3 h was higher in the PRAGUE-18 (OR [95% C.I.] 2.65 [2.03–3.47]). However, the percentage of patients with time-to-reperfusion >6 h was still significant (22.3 vs. 27.2% in PRAGUE-18). There was an increase in probability for an initial TIMI flow >0 in the later study (1.49 [1.0–2.23]), and also for an optimal procedural result (4.24 [2.12–8.49], p < 0.001). The risk of 30-day mortality decreased by 61% (0.39 [0.17–0.91], p = 0.029). Conclusion The prognosis of women with MI treated with primary PCI improved substantially with 24/7 regional availability of mechanical reperfusion, performance-enhancing technical progress, and intensive adjuvant antithrombotic therapy. A major modifiable hindrance to achieving this benefit in a broad population of women is the timely diagnosis by health professional services.